The Influence of Sport Education on Students' Social and Emotional Development - Andri Catur Trissetianto (Siber Nusantara Review, 2024)
This study investigates the impact of Sport Education on students’ social and emotional development in a middle school setting. Using a quasi-experimental design with pre- and post-tests, 60 students were divided into experimental and control groups. The experimental group participated in a 12-week Sport Education program, while the control group received traditional physical education. Data were collected using the Social-Emotional Competence Questionnaire (SECQ) and analyzed using paired sample t-tests and ANCOVA. Findings reveal that the Sport Education model significantly improved students’ competencies in self-awareness, self-management, social awareness, relationship skills, and responsible decision-making compared to the control group. The structured features of Sport Education—such as student roles, autonomy, and cooperative team dynamics—created a meaningful context for developing emotional intelligence and interpersonal skills. These results highlight the value of incorporating Sport Education into school curricula as a strategy for promoting holistic student development. This model offers a promising avenue for educators to nurture not only physical abilities but also essential life skills necessary for academic success and personal well-being.